The Preparation and Application of Diaryliodonium Salts Derived from Gemfibrozil and Gemfibrozil Methyl Ester - Zhou, Jun; Bao, Zhiyuan; Wu, Panpan; Chen, Chao (Synthesis, 2021)
The diaryliodonium salts derived from gemfibrozil and gemfibrozil methyl ester were synthesized from ArI(OH)OTs or bis(4-methoxyphenyl)iodonium diacetate with good regioselectivity. These iodonium salts were successfully used in the derivatization of gemfibrozil or gemfibrozil methyl ester, including fluorination, alkynylation, arylation, etherification, esterification, and iodination reactions.
Keywords: gemfibrozil; gemfibrozil methyl ester; diaryliodonium salts; Koser’s reagent; derivatization